Nutrient Balance from Agricultural Pollution Sources on Selected Tributaries to the Švihov Reservoir - Oppeltová, Petra; Kvítek, Tomáš; Kasal, Pavel (Mendelova univerzita v Brně, 2022)
Agriculture is the leading source of non-point sources of water pollution, especially in terms of the runoff process. Agricultural management promotes extensive water contamination, soil erosion and sedimentation in streams and reservoirs. The water reservoir Švihov on the Želivka river supplies drinking water to more than 1.5 million people. The catchment area of the water supply reservoir is intensively used for agriculture, more than 55% of the catchment area is arable land. Nutrients such as phosphorus and nitrates in the upper water-ways of tributaries are a huge problem. The aim of the research is to evaluate concentration trends and losses of nutrients (nitrates and phosphorus) at the chosen tributaries to the Švihov reservoir during 2018-2021. From the data on monthly concentrations and monthly discharges the monthly and annual losses of nitrates and phosphorus on each profile were calculated. The effect of discharges and concentrations on the magnitude of losses was investigated by correlation analysis. The influence of the forebay Trnávka dam on the magnitude of nutrient losses was also evaluated. The results show the importance of discharge magnitude on nutrient losses. The Trnávka forebay dam significantly reduces the transport of phosphorus from the Trnava catchment to the Švihov reservoir. In the catchment area of the reservoir it is recommended to implement nature-friendly and technical measures for water retention and accumulation in the landscape in order to reduce nutrient transport.
Keywords: agriculture; discharge; losses; nitrates; non-point sources; phosphorus; water retention